Visible light responsive strontium carbonate catalyst derived from solvothermal synthesis - Pornnaphat Wichannananon (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. A single crystalline phase of strontium carbonate (SrCO3) was successfully obtained from solvothermal treatments of hydrated strontium hydroxide in ethanol (EtOH) at 100◦C for 2 h, using specific Sr:EtOH mole ratios of 1:18 or 1:23. Other solvothermal treatment times (0.5, 1.0 and 3 h), temperatures (80 and 150◦C) and different Sr:EtOH mole ratios (1:13 and 1:27) led to formation of mixed phases of Sr-containing products, SrCO3 and Sr(OH)2 xH2O. The obtained products (denoted as 1:18 SrCO3 and 1:23 SrCO3), containing a single phase of SrCO3, were further characterized in comparison with commercial SrCO3, and each SrCO3 material was employed as a photocatalyst for the degradation of methylene blue (MB) in water under visible light irradiation. Only the 1:23 SrCO3 sample is visible light responsive (Eg = 2.62 eV), possibly due to the presence of ethanol in the structure, as detected by thermogravimetric analysis. On the other hand, the band gap of 1:18 SrCO3 and commercial SrCO3 are 4.63 and 3.25 eV, respectively, and both samples are UV responsive. The highest decolourisation efficiency of MB solutions was achieved using the 1:23 SrCO3 catalyst, likely due to its narrow bandgap. The variation in colour removal results in the dark and under visible light irradiation, with radical scavenging tests, suggests that the high decolourisation efficiency was mainly due to a generated hydroxyl-radical-related reaction pathway. Possible degradation products from MB oxidation under visible light illumination in the presence of SrCO3 are aromatic sulfonic acids, dimethylamine and phenol, as implied by MS direct injection measurements. Key findings from this work could give more insight into alternative synthesis routes to tailor the bandgap of SrCO3 materials and possible further development of cocatalysts and composites for environmental applications.